PANDEMY «COVID-19» IN AZERBAIJAN: MEDICAL AND LEGAL ASPECTS - Алієва, Айнура; Гусейнова, Фатіма; Алієв, Етібар (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose of the article: to consider the medical and legal aspects of the COVID-19 pandemic in Azerbaijan. It is noted that the semantic meaning of the term «pandemic» refers to the spread over a large territory, region, country, etc. infectious disease - an epidemic. Methods: the study was carried out using generally accepted methods of scientific knowledge, such as: analytical, comparative legal, semantic-cognitive, systemic, statistical and others. Results: in the country against this infectious disease at the level of the President of Azerbaijan and the Government of the Azerbaijan Republic, strict control is carried out and serious and effective measures are taken. A special quarantine regime has been declared on the territory of the Republic, legal liability of individuals and legal entities has been strengthened. Discussion: the main measures to combat the coronavirus pandemic, reducing its negative consequences. Currently, the world is suffering from coronavirus disease: a deplorable and tragic situation, numerous victims, health threats, deterioration of medical safety, closure of the borders of countries, mass scientific, cultural, sports, games, art and other events have been canceled. It is postponed, economic relations are limited, the real tourism sector has collapsed, educational institutions have been suspended, the form-septic industry is in danger, the world economy is in crisis, and the damage has exceeded hundreds of billions of dollars, etc. The negative consequences of this infection are inevitable. However, our country is effectively fighting the coronavirus both in law and in real life. In respect of persons violating quarantine norms and interfering with the normal work of medical personnel, strict punitive measures are taken in accordance with the requirements of the law. In the fight against the COVID-19 pandemic, everyone should exercise restraint, use psychological services, and not panic, protect themselves and their families, strictly following the requirements of the quarantine regime in isolation, and closely assist in this work. It is also important to remember that coronavirus can be defeated by following the rules of hygiene. If everyone demonstrates unity and solidarity and abides by the necessary rules in the fight against coronavirus, then the level of struggle and the measures taken will be high, the scope of the coronavirus will not spread, and our country will overcome this force majeure situation with little loss.